The Role of Taxation Problems on the Development of E-Commerce - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Nowadays e-commerce has become a vital part of our daily lives. The effects of globalization and rapid developments are experienced in knowledge and technology raises level of e-commerce. E-commerce provides businesses to sell their goods and services with a different method around the world and admits to consumers to access goods and services easily. Taxation of e-commerce is an important issue for countries, businesses and consumers who want to be a party of e-commerce. The issues such as tax loss and tax evasion are crucial in terms of countries. Difficulties like uncertainty and double taxation make parties of e-commerce reluctant and affect development of e-commerce negatively. In this study, the role of taxation problems on the development of e-commerce will be examined. We will aim to focus on how e-commerce can be developed with proper tax regulations. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: E-Commerce; Taxation; Double Taxation; Taxation Problems